(2,3)-generation of the groups PSL${}_4\big(2^m\big)$ (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
We prove that the group $PSL_4(2^m)$, $m>1$, is (2,3)-generated.